2008
DOI: 10.1111/j.1475-097x.2008.00833.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glibenclamide on acetylcholine and sodium nitroprusside induced vasodilatation in human cutaneous microcirculation

Abstract: K(ATP) channels play an important role in human cutaneous vasodilatation induced by ACh and SNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 56 publications
6
25
0
Order By: Relevance
“…; Hojs et al . ) in young adults. Because prostacyclin is a major COX‐derived vasodilator prostanoid, it is plausible that a relationship would exist between COX‐dependent cutaneous vasodilatation and prostacyclin production.…”
Section: Discussionmentioning
confidence: 97%
“…; Hojs et al . ) in young adults. Because prostacyclin is a major COX‐derived vasodilator prostanoid, it is plausible that a relationship would exist between COX‐dependent cutaneous vasodilatation and prostacyclin production.…”
Section: Discussionmentioning
confidence: 97%
“…K ATP channels contribute to resting vascular tone and tissue blood flow in the coronary (128, 305, 354, 407409, 641, 674, 995, 996, 1029, 1193, 1202, 1203, 1246, 1286, 1336, 1644), skin (2, 196, 613), splanchnic, and renal circulations (351, 614). In the heart it has been shown that the beating myocardium releases a K ATP channel agonist that activates these channels and dilates coronary arterioles (1376).…”
Section: Katp Channelsmentioning
confidence: 99%
“…; Orlov ) and K + channel inhibition typically causes an attenuated cutaneous vascular response (Hojs et al. ; Brunt and Minson ; Kutz et al. ), none have addressed their roles in cutaneous vasodilatation in humans during exercise.…”
Section: Introductionmentioning
confidence: 99%